A Therapeutic and Diagnostic Multidisciplinary Pathway for Merkel Cell Carcinoma Patients - Rastrelli, Marco; Del Fiore, Paolo; Buja, Alessandra; Vecchiato, Antonella; Rossi, Carlo Riccardo; Chiarion Sileni, Vanna; Tropea, Saveria; Russano, Francesco; Zorzi, Manuel; Spina, Romina; Cappellesso, Rocco; Mazzarotto, Renzo; et al. (Frontiers in Oncology, 2020)
Merkel Cell Carcinoma (MCC) is a highly aggressive neuroendocrine neoplasm of the skin. Due to its rarity, the management of MCC is not standardized across centers. In this article we present the experience of the Veneto region in the North-East of Italy, where a committee of skin cancer experts has proposed a clinical pathway for the diagnosis and treatment of MCC. Putting together the evidence available in the international literature, we outlined the best approach to the management of patients affected with this malignancy step- by- step for each possible clinical situation. Crucial in this pathway is the role of the multidisciplinary team to deal with the lack of robust information on each aspect of the management of this disease.